PENGEMBANGAN MEDIA BIG BOOK BERBASIS AUGMENTED REALITY MATERI TATA SURYA KELAS VI SEMESTER 2 - Rahma, Shofia; Yuli Witanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop Augmented Reality-based learning media called Big Book to improve learning outcomes of solar system material in grade VI of the Borg and Gall development model through 8 stages. First, the needs and problems analysis stage. Second, the data collection stage includes interviews, observations, questionnaires, tests, and documentation. Third, media product design. Fourth, the expert validation stage. Fifth, product revision. Sixth, the small-scale trial stage. Seventh, the final product assessment stage. Eighth, the large-scale trial stage. This study was limited to grade VI students of SDN Cepoko in Semarang City. The results showed that Big Book was included in the 'Very Eligible' criteria for use in learning based on the results of expert validation and materials. The completeness of student learning outcomes also increased significantly with the N-Gain value in the 'Medium' criteria. Big Book was assessed with teacher and student responses included in the 'Very Practical' criteria for use in science learning.